Effect of non-genetic factors on milk production of rural goats - GOKHALE, S B; RATHOR, B G; WADHER, M H; SHARMA, M S; RANGNEKAR, D V (The Indian Journal of Animal Sciences, 2013)
Milk yield data on 2 351 nondescript and graded Sirohi goats, kidding between 1991 and 1996 belonging to 262 farmersdistributed over 12 villages each of Asind and Mandai blocks in Bhilwara district of Rajasthan were analysed. The raw and least-squares mean lactation yield were 128.21 ± 1.43 kg and 114.22±22.62 kg in a lactation period of 167.28 ± 0.82 days respectiyely. The effects of location, village, parity, lactation period group, litter size, month and year of kidding, cast, land holding of the farmer, herd size of large and flock size of small animals maintained by the goat owner were highly significant. The effect of sex of kid and the family size of the goat owner did not have any effect on the milk yield of the goats. The milk yield increased with litter size. The low milk yield in first lactation significantly increased to second lactation. The lactation yield during second to fifth lactation did not differ. August to October kidding gave higher lactation yield compared to those kidding in other months of the year. The does kidded during 1995-96 produced more milk than those kidded during 1991-92 and 1993-94. The goats managedby Rabaries produced more milk yield and those owned by landless workers or farmers with less than 1 ha land gave highest lactation yield. The milk yield reduced with increase in land holding of the farmer. The goat owners who maintained a herd of more than 4 large animals reared their goats significantly better than those keeping small herd size. The highest milk yield was observed when flock size was 3-5 animals. The milk yield thereafter was found negatively correlated with the flock size.